UPAYA SEKOLAH DALAM MENANGKAL PAHAM RADIKALISME AGAMA MELALUI PROGRAM ROHIS DI SMA ISLAM ALMAARIF SINGOSARI - Moh Yusuf Kurniawan; Anwar Sa’dullah; Ika Anggraheni (Vicratina : Jurnal Ilmiah Keagamaan, 2020)
This study aimed to descibe the offorts the school in countracting the understanding of religious radicalism through the rohis program at Almaarif Singosari Islamic High School. The approach of qualitative research is used in this study,collecting data techniques used observation, interview, and docume nting. The result of this study show how schoos in countrecting radicalsm through the rohis program in the islamic High School Almaarif Singosari. Next is how school implement rohis program in school to countract radicalism. By implementing the Rohis program based on Ahlusunnah wal jamaah.